2014
DOI: 10.1177/2156869313520558
|View full text |Cite
|
Sign up to set email alerts
|

Is It Really Religion? Comparing the Main and Stress-buffering Effects of Religious and Secular Civic Engagement on Psychological Distress

Abstract: Using a random sample of adult residents from the state of Texas, we examine how religious participation and secular civic engagement buffer the effects of perceived financial strain and neighborhood disadvantage on psychological distress. Our findings suggest that (a) both organizational religious and secular civic engagement buffer the deleterious effects of perceived financial hardship on respondents’ psychological distress, (b) organizational as well as nonorganizational religious participation buffers the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
47
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 56 publications
(51 citation statements)
references
References 80 publications
1
47
0
Order By: Relevance
“…Our study adds an additional layer to this literature, demonstrating that individuals who disaffiliate but continue to maintain regular attendance experience no health or well-being disadvantage (Hypothesis 1a). This is significant given that secular sources of social engagement and social ties do not fully compensate for the absence of church-based social networks (Acevedo, et al, 2014). …”
Section: Discussionmentioning
confidence: 99%
“…Our study adds an additional layer to this literature, demonstrating that individuals who disaffiliate but continue to maintain regular attendance experience no health or well-being disadvantage (Hypothesis 1a). This is significant given that secular sources of social engagement and social ties do not fully compensate for the absence of church-based social networks (Acevedo, et al, 2014). …”
Section: Discussionmentioning
confidence: 99%
“…). Dimensions of religious involvement have also proven to buffer the adverse mental health effects of financial strain (Acevedo, Ellison, and Xu ; Bradshaw and Ellison ; Ellison, Burdette, and Hill ), living in a deteriorating and disordered neighborhood (Acevedo, Ellison, and Xu ; Krause ), traumatic life events (DeAngelis and Ellison ; Ellison ), and even hardships experienced during childhood (Henderson ; Jung ). These studies—and many others like them—provide empirical precedent for exploring whether religious involvement could also alleviate the heartache of dashed dreams.…”
Section: Introductionmentioning
confidence: 99%
“…Another concern is whether one's perceived relations with God are uniquely religious or instead merely reflect concrete relations with significant social others (e.g., (Spilka et al 1975;Pollner 1989;Acevedo et al 2014)). To rule out this possibility, we also controlled for indexes of family cohesion and friend support.…”
Section: Social Resourcesmentioning
confidence: 99%
“…Thanks to the pioneering work of Kenneth Pargament and colleagues, social behavioral scientists are becoming increasingly aware of religion's formidable role in the coping process (Pargament 1997;Ellison and Henderson 2011;Koenig et al 2012). Studies in this field have shown, for example, that numerous dimensions of religious involvement can buffer or offset the psychosocial strains of traumatic life events (Ellison 1991), neighborhood disadvantage (Acevedo et al 2014;Krause 1998), financial hardship (Acevedo et al 2014;Krause 2003), and interpersonal conflicts such as experiences of discrimination (Bierman 2006;Ellison et al 2008). …”
Section: Introductionmentioning
confidence: 99%